2009
DOI: 10.1021/cg800754b
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ferromagnetism in Cobalt-Doped LiNbO3 Single Crystalline Films

Abstract: Cobalt-doped (5 at. %) LiNbO3 (Co:LN) single crystalline films were prepared by combinatorial laser molecular-beam epitaxy on Al2O3 (001) substrates. The oxygen atmosphere should be severely controlled to be approximately 10 Pa to obtain stoichiometric Li/Nb concentration. Determined by asymmetric X-ray diffraction and high-resolution transmission electron microscopy, the epitaxial relationship of the sample follows (003)<100>F ∥ (003)<100>S, (110)<001>F ∥ (110)<001>S, and (113)<1̅10>F ∥ (113) <1̅10>S (F and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…They also found the same behavior in cobalt doped (5 at.%) LN single crystal films. [6][7][8] This magnetism has been attributed to point defects at the surface of the NPs.…”
Section: Multiferroic Response Of Nanocrystalline Lithium Niobatementioning
confidence: 99%
“…They also found the same behavior in cobalt doped (5 at.%) LN single crystal films. [6][7][8] This magnetism has been attributed to point defects at the surface of the NPs.…”
Section: Multiferroic Response Of Nanocrystalline Lithium Niobatementioning
confidence: 99%
“…However, recently some efforts have been put on as-obtained coarse LN particles that show ferromagnetism at RT. On an investigation carried out in 2018 by our group, it was found that the generation of oxygen vacancies-by thermal treatment in reducing atmospheres: thermal treatment in a reducing atmosphere (TTRA)-at the surfaces of LN:Fe powders is a mechanism that favors RT ferromagnetism at low doping concentrations of 0.44%, 0.89%, 1.47%, and 2.20% by mass of Fe2O3 (labeled as nLN:Fe-0.44-R, nLN:Fe-0.89-R, nLN:Fe-1.47-R, nLN:Fe-2.20- There is a tendency in what respects doped-LN to study single-crystal and polycrystal thin films, in comparison to polycrystalline powders; further results on the Fe impurity and reports on the doping with Co, Cu, and V-based on similar studies to those above just described-can be consulted in the literature [198,[202][203][204][205][206][207]. However, recently some efforts have been put on as-obtained coarse LN particles that show ferromagnetism at RT.…”
Section: Dilute Magnetic Oxides and Ferromagnetism In Linbo 3 Doped With Magnetic 3d Cationsmentioning
confidence: 98%
“…Figure 11 shows the plots of magnetic moment per transition metal-cation of LN doped with Fe (1-LN:Fe), Mn (2-LN:Mn), V (7-LN:V), as well as four different systems of LN doped with Co (labeled as 3-LN:Co, 4-LN:Co, 5-LN:Co, and 6-LN:Co). All samples were prepared as layers by different methods [190,192,198,[202][203][204][205]. As can be seen, for 2-LN:Mn and 7-LN:V, the AMM increases as the x increases until reaching a maximum; after that, the AMM begins to decrease as x increases.…”
Section: Dilute Magnetic Oxides and Ferromagnetism In Linbo 3 Doped With Magnetic 3d Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…多铁材料指材料具有两种或者两种以上的铁性 有序,铁性有序包括铁电性、铁磁性和铁弹性等。 多铁材料可以被广泛地应用在多态存储器、磁电探 测器和传感器等领域 [1][2][3][4] 。近几十年来,多铁材料被 认为是最具潜在应用价值的信息功能材料之一,受 到了科研人员的广泛关注。 ABO3 型钙钛矿氧化物材料具有独特的晶体结 构和丰富的物理性质,是当前多铁研究领域的热点 之一。其中,BiFeO3 是目前研究较多的多铁材料, 但 BiFeO3 在室温下是反铁磁性, 一定程度上限制了 其应用。 BaTiO3(BTO)是 ABO3 型钙钛矿结构的典型 铁电材料,在室温下具有强铁电性、热释电性、光 催化特性、高介电常数和高光电系数等优点 [5][6][7] 。 BTO 在室温下具有良好的铁电性, 却没有铁磁性 [8] , 这归因于铁电性和铁磁性在钙钛矿氧化物形成机制 上表现出的互斥性。铁电性的形成要求钙钛矿氧化 物在 B 位的过渡金属离子具有空的 d 轨道 [9] ;而磁 性的形成机制是要求处于 B 位的过渡金属离子的 d 轨道被电子部分占据 [10] 。这种互斥性仅表现在单相 中,可通过在材料不同单元分别引入铁电性与铁磁 性,实现材料整体的多铁性。人们在对 BTO 多铁性 的研究上尝试了许多方法,Hiroyuki 等 [11] 通过理论 计算预测了 Mn、 Fe 等掺杂的 BTO 能够实现多铁性, Song 等 [12] 通过对 LiNbO3 进行 Co 掺杂,实现了铁 电性和铁磁性的共存,引起了人们用过渡金属离子 掺入钙钛矿氧化物的方式来诱发多铁性的兴趣。不 同的过渡金属元素 Fe、Ni 掺杂 ABO3 钙钛矿型铁电 体证明了其可以实现室温铁磁性 [13][14] 。研究表明, 少量的 Fe 或 Mn 离子的掺杂使 BTO 的晶体结构从 四方转为六方相,Dang 等 [15] 制备出 BaTi1-xMnxO3 陶瓷,发现掺杂量 x 大于 0.01 就会产生六方相,而 铁电性就会有大幅的降低。多位研究者 [16][17][18][19][20][21] [12] 。即使很少的掺杂量也会使 BTO 的晶 体结构快速从四方相完全转变为六角相,四方相是 铁电相而六角相是顺电相。 Das 等 [22] 对 BTO 采用了 Mn-Nb 共掺杂的掺杂方式,抑制了六方相的产生, 使晶体结构较为缓慢的由四方相到立方相的转变。 过渡金属离子与 Nb 共掺杂的策略可以在诱导出铁 磁性的同时也一定程度上抑制铁电性的减弱。 另外, Nb 5+ 的 d 轨道上的电子为空, 这也会增强铁电性 [9] 。 从过渡金属元素的单掺杂到过渡金属元素与 Nb 的 共掺杂这种掺杂策略调整给铁磁性的诱导和铁电性 的减弱之间增加更大的调整空间。Zheng 等 [23][25][26] 。 拉曼(Raman)散射光谱可以分析样品的晶体结 构和相变,不同掺杂陶瓷样品的拉曼光谱如图 2 所 示。 BTO 陶瓷的拉曼光谱中, 低中频区域(<500 cm -1 ) 显示有两个拉曼峰,269 cm -1 处峰的 A1(TO2)振动模 式和 306 cm -1 处峰的 B1(TO2)、E(TO2+LO2) 振动模 式;高频区域(>500 cm -1 ),A1(TO3)和 A1(LO2)振动 模式和氧八面体有关 [23,27] 。BTO 陶瓷样品的拉曼峰 窄而尖锐,表明样品的晶体结晶质量较好。在 305 cm -1 处的峰与样品的铁电性相关 [28] 。从图 2 可以看 出,三组掺杂样品的拉曼光谱在 305 cm -1 对应峰的 峰型变得平缓并且峰强减弱,说明具有铁电性的四 方相减少而顺电相的立方相增加,这是晶体结构从 四方相到立方相转变的明显标志 [29][30] 。同时 305…”
unclassified